Porphyrin-associated fluorescence spectroscopy (Photogen®) for the optical diagnosis of dental biofilm in orthodontic treatment: An observational clinical trial - Ravazzi, Rodrigo; Neves, José Guilherme; Santamaria, Mauro Pedrine; Rosa, Luciano Pereira; Rosa, Francine Cristina Silva; Santamaria-Jr, Milton [UNESP] (Elsevier, 2023)
Objective: : This study assessed the presence of dental biofilm with fluorescence spectroscopy associated with porphyrin (Photogen®) in users of orthodontic appliances. Methods: : This cross-sectional observational clinical trial included 21 patients with metallic orthodontic fixed appliances. The presence of biofilm was evaluated by fluorescence spectroscopy (Evince—MMÓptics. São Carlos-SP, Brazil) with a porphyrin photo-evidence device (Photogen®). Digital images of the buccal surface of the upper anterior teeth (central and lateral incisors and canines) without and with porphyrin were analyzed using the histogram R (red) function in ImageJ software. The results were analyzed using the maximum and mode values of the red pixels from the histograms. The statistical analysis considered the significance level of 5%. Results: : The maximum values and modes of the red pixels were significantly higher in biofilms analyzed by porphyrin-associated optical spectroscopy compared to optical spectroscopy alone. Conclusions: : Porphyrin-associated fluorescence spectroscopy was able to detect dental biofilm in the oral environment of patients with orthodontic treatment. This method better evidenced the presence of biofilm on the buccal surfaces of the upper teeth compared to that observed with fluorescence spectroscopy without porphyrin.
Keywords: Biofilm; Fluorescence; Orthodontics; Porphyrin; Spectroscopy